Prostitusi Online: Penjualan Suami Oleh Istri (Perubahan Relasi Gender dan Seksualitas di Era Digital) - Susanti, Vinita (UI Scholars Hub, 2020)
This article discusses online prostitution in the digital age, by showing changes in gender relations between victims and perpetrators, which are analyzed with the view of radical feminists and Bourdieu's theory, symbolic violence. Women in gender ideology are placed as victims, so in this article there is social deconstruction, where women occupy positions as perpetrators. This change was demonstrated through an online prostitution case: the selling of a husband by a wife. The discussion begins with the case of online prostitution, women in reality studies: victims of online prostitution, the study of radical feminist thought and symbolic violence from Bourdieu's theory in the context of online prostitution and changes in gender relations in the context of online prostitution. The purpose of writing this article is to make academic contributions in the development of sociological studies, specifically in gender sociology.